Common sense paper and pencil assessments - Stiggins, Rick; Assessment Training Institute (Portland, Oregon : Assessment Training Institute, 1999)
This training video shows how effective classroom assessment techniques can increase student's willingness to take responsibility for their own learning and can help them achieve in school
Title from cover
Presenter: Rick Stiggins
Keywords: Examinations -- Design and construction; Grading and marking (Students); Educational evaluation